(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
A phraseological unit is a linguistic unit consisting of two or more word components which represents a single meaning with a particular figurative meaning, such as to flog a dead horse, as happy as Larry, to be snowed under. Nowadays, the cultural viewpoint and the structural and semantic analysis of phraseological units with a particular component has been in the limelight. In this article, the participation of personal names in the linguistic field of phraseological units as the representation of culture with examples and analyses in sentences has been discussed.